1994
DOI: 10.1159/000168681
|View full text |Cite
|
Sign up to set email alerts
|

Histological, Radiological, and Biochemical Features of the Adynamic Bone Lesion in Continuous Ambulatory Peritoneal Dialysis Patients

Abstract: Adynamic bone is being found with increasing frequency in dialysis patients. Little is known about its aetiology, and even less about its natural history. We found 10 cases of asymptomatic adynamic bone among a group of 32 continuous ambulatory peritoneal dialysis patients, most of whom had never been exposed to aluminium-containing phosphate binders. Compared to the remaining 22 patients, they had an older mean age (54 ± 11.4 vs. 42 ± 11.8 years; p < 0.05), probably a longer pre-dialysis duration of renal fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…In common with aluminum-related ABD, non-aluminum ABD is characterized by a tendency to hypercalcemia and metastatic calcification [12, 13], and there is therefore a potential risk of calciphylaxis and arteriosclerosis. By definition, the ability of bone to buffer a calcium load should be reduced in ABD, and this is indeed found to be the case [14].…”
Section: Is It a Disease?mentioning
confidence: 99%
See 2 more Smart Citations
“…In common with aluminum-related ABD, non-aluminum ABD is characterized by a tendency to hypercalcemia and metastatic calcification [12, 13], and there is therefore a potential risk of calciphylaxis and arteriosclerosis. By definition, the ability of bone to buffer a calcium load should be reduced in ABD, and this is indeed found to be the case [14].…”
Section: Is It a Disease?mentioning
confidence: 99%
“…In theory, a reduced bone turnover will reduce the capacity of bone to repair microfactures, resulting in an increased fracture risk independent of bone mass. No particular effect of ABD on bone mineral density (BMD) should be expected, and this is generally found to be the case [12, 20, 21]. Indeed, one study [12]found the development of ABD to be associated with a rising BMD.…”
Section: Is It a Disease?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been an increase in the prevalence of ABD in dialysis patients [4], and low PTH levels are frequently seen in chronic renal failure patients with ABD [4]. In addition, it has been reported that ABD is associated with increased fracture rate [5], brittle calcium control [6] and increased vascular calcification [7]. Since vascular calcification is currently recognized as a risk factor for mortality in patients with end-stage renal disease [8], elucidating the mechanisms underlying the development of ABD is essential to improve quality of life and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Adynamic bone is characterized by low to normal serum intact parathyroid hormone levels (PTH), low alkaline phosphatase, and episodes of hypercalcemia (3,4). In the skeleton, there is diminished bone formation rate, a decrease in osteoblast and osteoclast number, and a decline in osteoid formation (4 -6).…”
mentioning
confidence: 99%